DIGITAL ECONOMY AND ECONOMIC EFFICIENCY: THE STRATEGIC IMPORTANCE OF TECHNOLOGICAL CHANGE - Normurodov Sardorbek Bahodirovich (Journal of Applied Science and Social Science, 2026)
This article examines the development of digital technologies and their impact on economic efficiency. The study analyzes in a simple and understandable way how digital changes affect the economy. Attention is paid to the fact that the rapid development of information and communication technologies makes production processes more efficient, reduces costs, and improves management systems. It also argues that digital technologies play an important role in accelerating economic growth. The article analyzes the changes taking place in the labor market in the digital economy, the emergence of new professions, and the decrease in demand for certain professions. In addition, issues such as cybersecurity problems, digital inequality, and social problems are also considered. The results of the study show that the correct and effective implementation of digital technologies is important in ensuring economic stability, increasing competitiveness, and having a positive impact on the country's development.